2021
DOI: 10.1039/d1cp01585k
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the photo-orientation rate of an azobenzene-containing polymer based on a kinetic model of photoinduced ordering

Abstract: The explicit dependence of the rate of photoinduced ordering (photo-orientation) of azobenzene-containing liquid-crystalline polymer on photostationary concentration of cis-azobenzene has been predicted theoretically and found experimentally. The employed kinetic model...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…The described mechanism was corroborated by the measurement of the orientation distribution function of the material in the course of photoorientation 18 by the direct microscopic observation of the growth and diminishing crystallites 22 and by correlating the photo-orientation rate with the photostationary concentration of the cis-isomer in the irradiated sample. 23 We believe that the S-shaped kinetics of dichroism observed for complex I further corroborates the described mechanism of the photo-orientation process.…”
Section: Complexsupporting
confidence: 80%
See 1 more Smart Citation
“…The described mechanism was corroborated by the measurement of the orientation distribution function of the material in the course of photoorientation 18 by the direct microscopic observation of the growth and diminishing crystallites 22 and by correlating the photo-orientation rate with the photostationary concentration of the cis-isomer in the irradiated sample. 23 We believe that the S-shaped kinetics of dichroism observed for complex I further corroborates the described mechanism of the photo-orientation process.…”
Section: Complexsupporting
confidence: 80%
“…The described unusual behavior is analogous to the course of solid-phase (topochemical) reactions and to the kinetics of phase transitions when processes occur through the nucleation and growth of nuclei of a new phase. 20,21 We previously showed that the photo-orientation of polymers and low-molecular-weight liquid-crystalline materials proceeds by a rearrangement of their domain or microcrystalline structure: 12,22,23 upon irradiation with light, domains or crystallites oriented parallel to the electric vector of the irradiated light contain larger amounts of the cis-isomer of the azobenzene chromophore and thus are less stable compared with perpendicularly oriented domains. As a result of irradiation, the size and number of less-stable domains decrease, whereas domains or crystallites with a perpendicular orientation grow.…”
Section: Complexmentioning
confidence: 99%